Identification of Antiestrogen‐Bound Estrogen Receptor α Interactomes in Hormone‐Responsive Human Breast Cancer Cell Nuclei. Issue 19 (16th September 2020) - Gigantino, Valerio; Salvati, Annamaria; Giurato, Giorgio; Palumbo, Domenico; Strianese, Oriana; Rizzo, Francesca; Tarallo, Roberta; Nyman, Tuula A.; Weisz, Alessandro; Nassa, Giovanni
Abstract: Estrogen receptor alpha (ERα) is a ligand‐inducible transcription factor which mediates estrogen actions in hormone‐responsive tumors and is targeted by effective anticancer therapies based on the ERα antagonist ligands, selective estrogen receptor modulators (such as Tamoxifen/TAM) or disruptors (such as Fulvestrant/ICI). Despite its importance for cancer therapy, including acquired resistance to endocrine therapy, the molecular basis of ERα response to different ligands is not fully known to date. Interaction proteomics shows great potential to identify and characterize molecular mechanisms of disease based on physical and functional protein‐protein interaction networks. Tandem affinity purification coupled to mass spectrometry is applied here for mapping in hormone‐responsive breast cancer cells nuclei, the ERα interactomes, induced by each of the two classes of antiestrogens. The results provide new insights on the molecular bases for antiestrogen‐mediated control of ERα function and reveal new potential ways to overcome endocrine therapy resistance in cancer.